USING ELECTRONIC CAMBRIDGE DICTIONARY IN TEACHING ENGLISH PRONUNCIATION: PRE- EXPERIMENTAL STUDY ON THE SECOND YEAR OF SEKOLAH MENENGAH ATAS NEGERI 2 SINTANG - Agustinus Marjun (Edumedia : Jurnal Keguruan dan Ilmu Pendidikan, 2020)
This research objective was to identify whether the use of Audio CALD3 is effective in teaching students to pronounce minimal pairs of English word toward second year of SMA Negeri 2 Sintang. The sample chosen through cluster random sampling. They were 32 students selected as participant. The research finding showed the pre-test result was 55.63 and post-test result was 84.76 by applying 0.05 level of significance with 31 degree of freedom (df), the t-counted 25.778 was higher than t-table 2.042. It indicated that the use of Audio CALD3 is effective in teaching students to pronounce minimal pairs of English word. Key words: Pronunciation, the atsecond year of students, CALD3, Pre-experimental research design.